Memetakan Pendapat Ulama Untuk Pencegahan Praktik Pelukaan dan Pemotongan Genitalia Perempuan (P2GP): Memetakan Pendapat Ulama untuk Pencegahan Praktik P2GP - Mufliha Wijayati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2023)
Female genital mutilation and mutilation (FGM/C), which is better known in the community as circumcision or female circumcision, has become a global issue and is increasingly coming to the fore as a culturally harmful practice. The diversity of FGM/C practices with different implications gives a negative image to Islam which is considered to legalize or order female circumcision as an obligation for men. This article aims to map the opinions of Islamic scholars about FGM/C, from the opinions of fuqaha to contemporary scholars, both personally and collectively. Based on a review of kinds of literature, this article found a variety of opinions regarding female circumcision from the perspective of Islamic scholars; obligatory, sunnah, or dignity (makrumah). This research also shows the opinion of contemporary scholars who tend to say the weak argumentation of the dalil naqli that makes female circumcision obligatory. Based on maqasid sharia and medical evidence that circumcision does not benefit women and even tends to be harmful, contemporary scholars have issued a fatwa for its prohibition. The significance of this study lies in its usefulness as a basis for advocating the prevention of FGM/C practices in the community.